PROFIL PENGAJUAN SOAL MAHASISWA CALON GURU BERKEMAMPUAN RENDAH - Yudianto, Erfan (Jurnal Ilmiah AdMathEdu, 2012)
The research was moticated by the difficulty of students to solve mathematical problems, especially in the material derivative. Based on preliminary data obtained from research experience in teaching, students confusion in understanding the intent of the question whether the proposed teacher and from textbooks.  One alternative could be done to help students by rewriting the problem with his own words or write about in other forms. Hence the need for prospective teachers knowledge about the strategy. The purpose of this study to describe the profile of the submission of profpective teachers about students assessed based on mathematically ability. The resultsare expented to be utilized by the student teacher candidates to be applied in teaching and learning activities in schools. This study uses tests and interviews. Tests of the information given to prospective teachers and students the information is processed into a problem. Information given to the students of mathematics teacher candidat capable low as a research subject. Interviews were conducted to students of mathematics